The Syair Tabut of Encik Ali: A Malay account of Muharram at Singapore, 1864. Issue 133 (2nd September 2017) - Byl, Julia; Halid, Raja Iskandar bin Raja; Lunn, David; McCallum, Jenny
ABSTRACT: This is an annotated transcription and translation of the Syair Tabut (Poem of the Tomb Effigies) of Encik Ali, a Malay-language, Jawi-script syair account of the Muharram commemorations of 1864 at Singapore. The only known part lithograph and part manuscript of this text, on which this edition is based, is held in the library of Leiden University, shelfmark Kl. 191. For a full discussion of this Syair, see the accompanying article by Lunn and Byl (2017).